IMPLEMENTASI KEBIJAKAN PENANGGULANGAN HIV/AIDS DI KOTA MANADO - AMU, IRFAN; LENGKONG, FLORENCE; TAMPI, GUSTAAF (JURNAL ADMINISTRASI PUBLIK, 2020)
HIV control in Indonesia has been noted to have improved from itâ€™s implementation. Various HIV services have grown and the number of people using them has also increased rapidly. This led the Health Minister issued a Health Minister Regulation No. 21 of 2013 on HIV/AIDS prevention. But, as practice, every region has a yearly rise in HIV/AIDS cases. The purpose of the study is to find out how implementation of the HIV/AIDS prevention policies in Manado can be. The experimental concept used in this research is to take a kind of qualitative research with a descriptive approach. Then data-collection techniques will done by interviews, observations and documentaries. The technique for data-analysis in this research used Miles’ and hubennan’s qualitative data analysis. The results showed that the implementation of HIV / AIDS prevention policies in Manado was classified as good in terms of communication between the government and the targets that had been carried out, but for human resources in HIV/AIDS prevention it was still considered to be less than optimal. Whereas with a very supportive sense of execution, and SOP that conforms to health care standards and has associated coordination with stakeholders. So it should be concluded that the implementation of the HIV/AIDS prevention policies in Manado has not been fully implemented. Keywords : Policy Implementation, Prevention, HIV / AIDS